APPLYING ARDUINO FOR CONTROLLING CAR PARKING SYSTEM - AL-TABATABAIE, Kusay F.; ABDULAMEER, Sadeer D. (Applied Computer Science, 2019)
With increasing automobiles in the parking space, we could face problems like unplanned parking, lack of discipline, wasting time and fuel while looking for free space around the parking ground. These problems could be solved by applying Arduino for controlling car parking system. The proposed system will detect an available parking slot in short time, saves fuel, offer monitoring car parking system with low consumption, easy to implement and inexpensive.